Cardiorespiratory Fitness Normative Values in Latin-American Adolescents: Role of Fatness Parameters - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The aim of this study was to provide percentile values for a cardiorespiratory fitness (CRF) field test for Latin-American adolescents (34,461 girls and 38,044 boys) aged 13 to 15 years. The role of fatness parameters on the CRF level across age groups was also examined, with a focus on non-obese (healthy) and obese groups. CRF was assessed using the 20-meter shuttle run test protocol. Anthropometric parameters were measured using body mass index z-score (body mass index (BMI) z-score), BMI, waist circumference (WC), and waist-to-height ratio (WHtR). Participants were categorized according to the BMI z-score, WC, and WHtR international cut-off points as healthy and obese. Age-and sex-specific reference tables for the 3rd, 10th, 25th, 50th, 75th, 90th, and 97th centile scores were calculated using Cole’s lambda, mu, and sigma method. The prevalence of obesity according to the BMI z-score, WC, and WHtR was 9.6%, 11.2%, and 15.0%, respectively. Across all age and sex groups, a negative association was found between relative peak oxygen uptake (VO2 peak) and BMI, WC, and WHtR. In boys and girls there were higher levels of performance across all age groups, with most apparent gains between the ages of 13 and 14 years old. Overall, participants categorized in the healthy group had shown to have significantly higher VO2 peak than their obese counterparts (p < 0.001; Cohen’s d > 1.0). In conclusion, our study provides age-and sex-specific reference values for CRF (VO2 peak, mL·kg−1·min−1 ). The anthropometric parameters were inversely associated with CRF in all ages in both sexes. The obese group had worse CRF than their healthy counterparts independent of anthropometric parameters used to determine obesity. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.